2009
DOI: 10.1107/s1744309109044741
|View full text |Cite
|
Sign up to set email alerts
|

Role of tyrosine 131 in the active site of paAzoR1, an azoreductase with specificity for the inflammatory bowel disease prodrug balsalazide

Abstract: Azoreductase 1 from Pseudomonas aeruginosa strain PAO1 (paAzoR1) catalyses the activation of the prodrug balsalazide and reduces the azo dye methyl red using reduced nicotinamide adenine dinucleotide cofactor as an electron donor. To investigate the mechanism of the enzyme, a Y131F mutation was introduced and the enzymic properties of the mutant were compared with those of the wild-type enzyme. The crystallographic structure of the mutant with methyl red bound was solved at 2.1 A resolution and compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…The K m value for DCIP with paAzoR1 is similar to those obtained for azo compounds: 85.3 ± 3.6 μM for DCIP compared to 98.6 μM for balsalazide (Wang et al, 2010a). The V max value is similar to those observed for azo substrates: V max = 0.53 ± 0.01 μM/s for DCIP compared to 0.81 μM/s for balsalazide (Wang et al, 2010a).…”
Section: Nad(p)h Quinone Oxidoreductase Activitysupporting
confidence: 77%
See 3 more Smart Citations
“…The K m value for DCIP with paAzoR1 is similar to those obtained for azo compounds: 85.3 ± 3.6 μM for DCIP compared to 98.6 μM for balsalazide (Wang et al, 2010a). The V max value is similar to those observed for azo substrates: V max = 0.53 ± 0.01 μM/s for DCIP compared to 0.81 μM/s for balsalazide (Wang et al, 2010a).…”
Section: Nad(p)h Quinone Oxidoreductase Activitysupporting
confidence: 77%
“…The azoreductase reaction is proposed to be catalyzed via a Bi-Bi ping-pong mechanism (Nakanishi et al, 2001;Liu et al, 2008;Wang et al, 2010a), and we have indicated that the reaction is likely to occur via reduction of the hydrazone tautomer of the substrate, as identified from structural studies ( Fig. 1A) (Ryan et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Two broad types of azoreductases including flavin-dependent and non-flavin reductases have been reported (Blumel & Stolz, 2003;Maier et al, 2004;Suzuki et al, 2001). Flavin-dependent azoreductases usually reduce azo dyes through a Ping-Pong Bi-Bi mechanism (Nakanishi et al, 2001;Ryan et al, 2010;Wang et al, 2010). In this mechanism, two cycles of NADPH-dependent reduction of FMN to FMNH occur, converting azo dye to a hydrazine in the first step, and then the hydrazine to two constitutive amines in the second step (Correia et al, 2011;Ryan et al, 2010).…”
Section: Reductive Enzymesmentioning
confidence: 99%